(untitled) (Malaysian Journal of Learning and Instruction, 2024)
Purpose - The language load within mathematics test items can lead to inaccuracy in assessing Orang Asli pupils’ mathematical ability due to their struggle in comprehending the academic language. This study aims to determine the validity of using test accommodations in the form of oral academic language and oral native language when administering mathematics computation and word problem test items among the Orang Asli pupils. Methodology - By employing a quantitative approach, this study utilised random equivalent group design to examine the validity of using oral test accommodations among 334 Grade Four Orang Asli pupils. Three testlets were constructed and used in this study: written test in the academic language (WAL), oral test in the academic language (OAL), and oral test in the native language (ONL). The three testlets comprised Paper 1 and Paper 2, each consisting of 20 mathematics computation and 20-word problem test items, respectively. One-way ANOVA was used to analyse and examine if there were differences in the mathematics performance between the three groups of tests administered to the Orang Asli pupils. Findings - The results indicated that the test scores of the pupils on the oral tests were higher compared to the written test administered to the pupils for both mathematics computation and word problem items. For computation items, the pupils performed better in the OAL testlet, followed by the ONL testlet. On the other hand, the pupils obtained the highest test scores in the ONL testlet compared to the OAL testlet for word problem items. Furthermore, the results illustrate that there is a difference in the mathematics performance of the Orang Asli pupils between the oral tests in both languages and written tests in the academic language. Significant - This study clearly shows that language plays a prominent role in affecting the Orang Asli pupils’ mathematics performance. By utilising the oral test as a promising test accommodation, this measure could help address the language barrier faced by the Orang Asli pupils in mathematics testing.